Orientacion del mejoramiento de frijoles volubles - Davis, J.H.C. (International Center for Tropical Agriculture, 1979)
The method of selection used by CIATs climbing bean program is between the pedigree method (lineage) and the bulk population method. This method reduces the variation of each hybrid population in F, by individual selection. The evaluation of the germplasm bank was conducted in Popayan (1850 m above sea level), Antioquia (2200 m above sea level) and Pasto (2700 m in alt.) to find disease-resistance, appropriate growth habit and adaptation. The selected var. were tested for resistance to BCMV races and anthracnose in the greenhouse. The appropriate method was backcrossing in this case. Crossbreeding followed by selection in the field is used to increase yield potential, the level of tolerance to certain diseases and adaptability. In maize/bean associations, it is recommended to select crosses or lines of 2 crosses together. The strategy of selection used is summed-up in table form. (CIAT)